The Upper Paralimbal Zone is Especially Susceptible to Ruptures Due to Blunt Trauma - Osterried, Lea; Gruber, Markus; Böhringer, Daniel; Agostini, Hansjürgen; Reinhard, Thomas (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Globe ruptures are ophthalmological emergencies where the primary diagnosis using a slit lamp is often a challenge.Objectives The retrospective case study aimed to characterise the predilection sites, the demographic profile and the causes of bursts due to blunt globe trauma.Materials and Methods The surgical plan of the Eye Centre of the Medical Centre (University of Freiburg) was electronically searched using the keyword “globe rupture” over a period of 18 years (2000 – 2018). This led to 350 hits, which were scrutinised by hand. 134 globe ruptures due to blunt globe trauma were then identified.Results The most common predilection sites were the upper nasal and the upper temporal paralimbal zones with 37 and 32% of the examined globe ruptures, respectively. The average age at the time of rupture was 60 (from 2 to 97) years. The median age was 62.5 years. 37% (49/134) of patients were female. The most frequent causes of accidents were falls (43%), “flying” wooden and metal objects (18%) and acts of violence (10%).Conclusions Special attention should be paid to the upper paralimbal zone in the exploratory primary care of globe ruptures. If the rupture occurred due to “flying” wooden and metal objects, the posterior sclera burst most frequently. The epidemiological data suggest that targeted prevention against falls for individuals over 60 years and consistent wearing of protective eyewear when working with wood or metal could reduce the incidence of bulbar bursting. It was also noticeable that acts of violence were the third most frequent cause of rupture, although woman did not report that they were affected by this. Given the high occurrence of violence against women, shame and stigma may lead to an incorrect inquiry about the cause of the accident. This could be mitigated by training employees specifically to take a sensitive history.
Keywords: trauma; globe rupture; sclera; falls